2019
DOI: 10.18203/2320-1770.ijrcog20192452
|View full text |Cite
|
Sign up to set email alerts
|

Level of serum uric acid in patients with preeclampsia compared to controls and its relation to feto-maternal outcome

Abstract: Background: Uric acid is the final product of the purine metabolism in humans. The two final reactions in its production which catalyze the conversion of hypoxanthine to xanthine and the latter to uric acid are catalyzed by the enzyme xanthine oxidoreductase. The role of uric acid in the progression of prediabetes to diabetes has been known. Serum uric acid has been shown to be associated with cardiovascular disease, hypertension, and chronic kidney disease. The present study was done to see the level of uric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…In addition, the study found that 12.3% of neonates were admitted in the neonatal intensive care unit. These ndings did not match with other studies done by Meena et al, India and Zangana et al, Iraq reporting a proportion of 34% and 57.48% NICU admissions respectively (13,15) Moreover, the proportion of deliveries before 37weeks of gestation in our study was found to be 70.9% among the subjects with hyperuricemia. This nding seem to be quite comparable with the proportion of preterm delivery 75.6% found in Maternity teaching hospital in Erbil, but in contrary to 43.2% by study done in Vietnam (9,13).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the study found that 12.3% of neonates were admitted in the neonatal intensive care unit. These ndings did not match with other studies done by Meena et al, India and Zangana et al, Iraq reporting a proportion of 34% and 57.48% NICU admissions respectively (13,15) Moreover, the proportion of deliveries before 37weeks of gestation in our study was found to be 70.9% among the subjects with hyperuricemia. This nding seem to be quite comparable with the proportion of preterm delivery 75.6% found in Maternity teaching hospital in Erbil, but in contrary to 43.2% by study done in Vietnam (9,13).…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the study done by Meena R et al, which showed that hyperuricemia in patients with hypertensive disorders during pregnancy was a strong risk factor for several maternal complications. [18] In the study done by Kumar and Singh, it was observed that a high uric acid level was associated with increased severity of the disease and adverse maternal outcomes. [7] Similarly, Kondareddy and Prathap have also shown that an increase in uric acid level is associated with increasing severity of pregnancy-induced hypertension like eclampsia, abruptio and HELLP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…18 A case control study from Ajmer observed marked difference between serum acid level in pregnant patients had pre-eclampsia and females with healthy pregnancy respectively 7.65 [+ or -] 081 mg/dl and 3.21 [+ or -] 072 mg/dl, (p value 0.001). 19 An outpatient department study was conducted at our fellow institution. They found significantly elevated level of serum uric acid in 63% pregnant women with pre-eclampsia in 3 rd trimester.…”
Section: Discussionmentioning
confidence: 99%